2006
DOI: 10.1007/s00383-006-1751-3
|View full text |Cite
|
Sign up to set email alerts
|

Conservative treatment of infantile hypertrophic pyloric stenosis with intravenous atropine sulfate does not replace pyloromyotomy

Abstract: Pyloromyotomy as described by Weber and Ramstedt has been the standard therapy for infantile hypertrophic pyloric stenosis since the 1960's and conservative therapy has been abandoned. The objective of this study was to test the effectiveness of systemic atropine applied intravenously for 7 days as a conservative therapeutic strategy and as an alternative to primary operation. Forty-two consecutive term infants with infantile hypertrophic pyloric stenosis were enrolled in the study over a period of 5 years. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 19 publications
2
36
0
Order By: Relevance
“…Three recent studies, conducted in diverse settings, have demonstrated that between 75 and 87% of infants affected by pyloric stenosis can be successfully treated without surgery, using intravenous atropine (Huang and Su, 2004;Meissner et al, 2006;Kawahara et al, 2005). This research lends support to the possibility that mild cases of pyloric stenosis may resolve without medical intervention.…”
Section: Discussionmentioning
confidence: 49%
“…Three recent studies, conducted in diverse settings, have demonstrated that between 75 and 87% of infants affected by pyloric stenosis can be successfully treated without surgery, using intravenous atropine (Huang and Su, 2004;Meissner et al, 2006;Kawahara et al, 2005). This research lends support to the possibility that mild cases of pyloric stenosis may resolve without medical intervention.…”
Section: Discussionmentioning
confidence: 49%
“…However, this particular study was very unclear regarding the amount of atropine used, and the small success rate may have been due to dosages below a therapeutic level. Even the study most critical of conservative treatment of IHPS, whose authors would not recommend conservative therapy in settings where surgery is possible due to length of treatment and lower success rates when compared to surgery, reported a success rate for the conservative approach of 75% 5. Furthermore, known side effects of atropine therapy, such as mild facial flushing, increased alanine aminotransferase and tachycardia, appear to be rare and not serious.
Figure 1 Forest plot.
…”
Section: Commentarymentioning
confidence: 99%
“…However, the success rate of medical treatment with atropine is lower than that of surgery (which is at least 95%5), and it requires longer hospitalisation because of intravenous therapy and the need to continue oral atropine after discharge, the latter requiring a lot of parental effort. Additionally, due to the lower success rate, patients whose symptoms do not resolve with atropine therapy, may then have to undergo surgery when their health has deteriorated even further.…”
Section: Commentarymentioning
confidence: 99%
“…Increased vascularity has been shown to be an integral component of the pylorus in IHPS 12 . An increased amount of desmin in the hypertrophied pylorus may be the cause of incoordination of contraction and relaxation 13 . Management has come a long way from simple observation to treatment with i.v.…”
Section: Discussionmentioning
confidence: 99%